2023
DOI: 10.3390/life13091929
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Partial Substitution of Chemical Fertilizer with Organic Fertilizer on Soil Organic Carbon Composition, Enzyme Activity, and Grain Yield in Wheat–Maize Rotation

Xiaoliang Li,
Junchao Fang,
Hiba Shagahaleh
et al.

Abstract: This study explored the effect of the long-term partial replacement of chemical fertilizer with organic fertilizer on soil organic carbon composition, enzyme activity, and crop yields in the wheat–maize rotation area of northern Anhui, China. This study also specified the proper amount of organic fertilizer replacement that should be used for chemical fertilizer. Different fertilization modes were used (no fertilization, CK; chemical fertilizer, CF; chemical fertilizer and straw returning, CF + S; chemical fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…The results of this study showed that application of organic manure significantly increased the activities of soil catalase, soil dehydrogenase, soil sucrase, urease and alkaline phosphatase compared to CK (Figure 4). This is mainly because organic fertilizer increases the soil organic carbon and nitrogen stocks which induces an increase in enzyme activity by increasing the substrate in the enzymatic reaction [50,51]. The comparison of different organic fertilizers revealed that that soil peroxidase and urease activities were higher in soil treated with commercial organic fertilizer, while soil glycosidase activities were higher in soils treated with corn stover and sheep manure, which is consistent with the results of previous studies [23].…”
Section: Effect Of Organic Fertilizer Application On Soil Fertility A...supporting
confidence: 89%
“…The results of this study showed that application of organic manure significantly increased the activities of soil catalase, soil dehydrogenase, soil sucrase, urease and alkaline phosphatase compared to CK (Figure 4). This is mainly because organic fertilizer increases the soil organic carbon and nitrogen stocks which induces an increase in enzyme activity by increasing the substrate in the enzymatic reaction [50,51]. The comparison of different organic fertilizers revealed that that soil peroxidase and urease activities were higher in soil treated with commercial organic fertilizer, while soil glycosidase activities were higher in soils treated with corn stover and sheep manure, which is consistent with the results of previous studies [23].…”
Section: Effect Of Organic Fertilizer Application On Soil Fertility A...supporting
confidence: 89%